Modula??o multiportadora M-QAM n?o quadrada modificada por blocos para canais com modelo de rummler - Fonseca, Leandro Coimbra da (2004)
Abstract: One of the main factors that cause degradation of the quality of digital systems long range in line of sight with transmission rates on the order of a few tens of Mb / s, are the selective fading in frequency. An alternative to reduce the effect caused by selective fading in frequency is coded using a multicarrier modulation of [6], [17]. This work aims to analyze the performance of a coded multicarrier modulation by low blocks complexity for M-QAM constellations (M-ary Quadrature Amplitude Modulation) best suited to non-square pipes with widths close to 29MHz bands. At the end of this study with the results obtained from computer simulations for BCMCM scheme (Block Coded Multicarrier Modulation) 128-QAM, using a simple code arrangement is compared with the BCMCM scheme 64-QAM presented in [6], [ 17], when observed, as well as reducing bandwidth used, a reduction of the system signature area. It was also analyzed the performance of a BCMCM 32-QAM system for a transmission rate of 51MB / s.